Pembuatan Bibliografi Beranotasi Skripsi Jurusan Teknik Elektro Tahun 2014-2016 Koleksi Ruang Baca Jurusan Teknik Elektro Universitas Negeri Padang - Indah, Nilam Sri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper aims to help users and librarian in the reading room of the Electrical Engineering Department in conducting a search of information or information retrieval. In this paper we describe the manufacture annotated bibliography of skripsi of Electrical Engineering Department in 2014â€“2016 Collections Reading Room of the Electrical Engineering Department of State University of Padang. The method used descriptive method. Information collected by observation. The results obtained in the direct observation, the number of skripsi collections in the reading room of the Department of Electrical Engineering of the year 2014-2016 is 157 title. Based on the discussion can be concluded the stage of making an annotated bibliography of skripsiÂ  of Electrical Engineering is as follows. First, the determination of title to the consideration of the availability of a collection of skripsi, applied the collection, the most demanding information, and information is still good and awake. Second, the collection of library materials by recording bibliographic data. Third, the selection of library materials be selected on the entire collection of skripsi by separating the skripsi is based on the order of years. Fourth, grouping or classification annotated bibliography of skripsi grouped by classification fundamental. Fifth, the keyword fabrication. Sixth, the preparation of the index. Seventh, typing the manuscript bibliography. Latest in the stage of making a bibliography is the examination of the final manuscript.Keywords: bibliography, annotated, electrical engineering department